RNA editing in response to COVID-19 vaccines: unveiling dynamic epigenetic regulation of host immunity - Jin, Yun-Yun; Liang, Ya-Ping; Pan, Jia-Qi; Huang, Wen-Hao; Feng, Yan-Meng; Sui, Wei-Jia; Yu, Han; Tang, Xiao-Dan; Zhu, Lin; Chen, Jian-Huan (Frontiers in Immunology, 2024)
Background COVID-19 vaccines are crucial for reducing the threat and burden of the pandemic on global public health, yet the epigenetic, especially RNA editing in response to the vaccines remains unelucidated. Results Our current study performed an epitranscriptomic analysis of RNA-Seq data of 260 blood samples from 102 healthy and SARS-CoV-2 naïve individuals receiving different doses of the COVID-19 vaccine and revealed dynamic, transcriptome-wide adenosine to inosine (A-to-I) RNA editing changes in response to COVID-19 vaccines (RNA editing in response to COVID-19 vaccines). 5592 differential RNA editing (DRE) sites in 1820 genes were identified, with most of them showing up-regulated RNA editing and correlated with increased expression of edited genes. These deferentially edited genes were primarily involved in immune- and virus-related gene functions and pathways. Differential ADAR expression probably contributed to RNA editing in response to COVID-19 vaccines. One of the most significant DRE in RNA editing in response to COVID-19 vaccines was in apolipoprotein L6 (APOL6) 3’ UTR, which positively correlated with its up-regulated expression. In addition, recoded key antiviral and immune-related proteins such as IFI30 and GBP1 recoded by missense editing was observed as an essential component of RNA editing in response to COVID-19 vaccines. Furthermore, both RNA editing in response to COVID-19 vaccines and its functions dynamically depended on the number of vaccine doses. Conclusion Our results thus underscored the potential impact of blood RNA editing in response to COVID-19 vaccines on the host’s molecular immune system.